Effect of axial compression ratio on concrete-filled steel tube composite shear wall. Issue 3 (February 2019) - Hou, Hetao; Fu, Weiqi; Qiu, Canxing; Cheng, Jirun; Qu, Zhe; Zhu, Wencan; Ma, Tianxiang
This study proposes a new type of shear wall, namely, the concrete-filled steel tube composite shear wall, for high performance seismic force resisting structures. In order to study the seismic behavior of concrete-filled steel tube composite shear wall, cyclic loading tests were conducted on three full-scale specimens. One conventional reinforced concrete shear wall was included in the testing program for comparison purpose. Regarding the seismic performance of the shear walls, the failure mode, deformation capacity, bearing capacity, ductility, hysteretic characteristics, and energy dissipation are key parameters in the analysis procedure. The testing results indicated that the bearing capacity, the ductility, and the energy dissipation of the concrete-filled steel tube composite shear walls are greater than that of conventional reinforced concrete shear walls. In addition, the influence of axial compression ratio on the seismic behavior of concrete-filled steel tube composite shear wall is also investigated. It was found that higher axial compression ratio leads to an increase in the bearing capacity of concrete-filled steel tube composite shear walls while a reduction in the ductility capacity.